Advances in Stem Cell Research - Baharvand, Hossein; Aghdami, Nasser; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2012)
Stem cells, whose impact will be revolutionary, provide enormous opportunities for both biological and future clinical applications. This book addresses state-of-the art concepts on stem cell nano-engineering, pluripotent stem cells, and cellular reprogramming as well as regenerative medicine. Advances in Stem Cell Research is an important volume, as it is comprehensive and covers all new aspects of stem cell biology, from basic research to clinical applications. There are 18 chapters written by internationally renowned stem cell scientists. This up-to-date text will give the reader a complete understanding of the exciting stem cell science and its applications. It will serve as a valuable reference for researchers and students. A valuable books for postgraduate students and advanced undergraduate students in cell biology, genetics, developmental biology, and biotechnology; stem cell researchers and clinicians; engineers in the field of regenerative medicine.
Embryonic Stem Cell Lines from Tetraploid Mouse Blastocysts -- The Significance of Culture Adaptation of Embryonic Stem Cells for Regenerative Medicine -- Biomanufacturing Human Pluripotent Stem Cells for Therapeutic Applications -- Human Embryonic Stem Cell-derived Hepatocytes -- Advances in Induced Pluripotent Stem Cell Biology -- Induced Pluripotent Stem Cells: New Applications for Metabolic Liver Diseases -- Vascular Differentiation of Human Pluripotent Stem Cells -- Mechanism of MicroRNA-mediated Global DNA Demethylation in Human iPS Cells -- Microtechnological Approaches in Stem Cell Science -- Application of Micro/Nanotechnology to Stem Cell Research and Technology -- Spermatogonial Stem Cells -- Cellular Reprogramming and Fate Conversion -- Omics in Stem Cell Therapy: The Road Ahead -- Microglia: The Bodyguard and the Hunter of the Adult Neurogenic Niche -- Immunosuppressive Properties of Mesenchymal Stromal Cells -- Cellular Therapy for Hematology Malignancies: Allogeneic Hematopoietic Stem Transplantation, Graft Versus Host Disease and Graft Versus Leukemia Effects -- Cardiac Versus Non-cardiac Stem Cells to Repair the Heart: The Role of Autocrine/Paracrine Signals -- Adult Neurogenesis in Alzheimer$1 (Bs Disease and Therapies.s
Keywords: Life sciences; Biotechnology; Cytology; Stem cells; Life Sciences; Stem Cells; Cell Biology; Biotechnology